The Influence of Theory of Planned Behavior and Technology Acceptance Models on Behavioral Intentions in Online Grocery Shopping in Pekanbaru City - Primaroni, Oky; Wijayanto, Gatot; Samsir, Samsir (MUI Kota Pekanbaru, 2024)
This study was carried out to investigate the impact of integrating two theories on consumer behavior, namely the Theory of Planned Behavior (TPB) and Technology Acceptance Models (TAM), on the consumer behavior intention in online food shopping in the city of Pekanbaru. A descriptive quantitative method was employed in this research, utilizing purposive sampling techniques. The study involved 174 female respondents aged 18 and above, residing in the city of Pekanbaru, who had previously engaged in online food shopping. The analysis of data was performed utilizing the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. The results indicated that both the perceived usefulness (PU) and perceived ease of use have a notable impact on attitude (ATT). Furthermore, behavioral intention was significantly influenced by attitude (ATT), subjective norm (SN), and perceived behavioral control (PBC). The originality of this study resides in combining the Theory of Planned Behavior (TPB) and Technology Acceptance Models (TAM) within the specific context of online food shopping in the city of Pekanbaru. This study is expected to contribute to the field of consumer behavior, especially the behavior of consumers in Pekanbaru regarding online food shopping.